Toni Erdmann [videorecording (DVD)] - Ade, Maren; Simonischek, Peter; Hüller, Sandra; Wittenborn, Michael, 1953- (Sony Pictures Home Entertainment, 2017)
Winfried doesn't see much of his working daughter Ines. He pays her a surprise visit in Bucharest, where she's busy as a corporate strategist. The geographical change doesn't help them to see more eye to eye. Practical joker Winfried annoys his daughter with corny pranks and jabs at her routine lifestyle of meetings and paperwork. Father and daughter reach an impasse, and Winfried agrees to go home to Germany. Enter Toni Erdmann: Winfried's flashy alter ego.